2015
DOI: 10.1007/s00436-015-4374-6
|View full text |Cite
|
Sign up to set email alerts
|

Review: Bucephalus minimus, a deleterious trematode parasite of cockles Cerastoderma spp.

Abstract: Trematodes are the most prevalent and abundant macroparasites in coastal waters. They display a complex life cycle with alternation of free-living and parasitic stages generally involving three host species. The most deleterious stage is in the first intermediate host (a mollusc) where the parasite penetrates as miracidium larvae and asexually multiplicates in sporocysts/rediae to provide cercariae larvae. However, due to basic low prevalence in ecosystems, this system remains difficult to study. Taking the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 84 publications
2
32
0
Order By: Relevance
“…Total prevalence of infection showed a seasonal pattern being highest in July (33%) and lowest in May (0%) as opposite to what was observed in Spain (Ramón et al 1999, Delgado andSilva 2018). Knowing that generally the prevalence of trematodes infecting bivalves as first intermediate host is positively correlated to host size (Magalhães et al 2015), the observed seasonal pattern could be related to the shell length confounding factor. Despite the clams sampled in May (B.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Total prevalence of infection showed a seasonal pattern being highest in July (33%) and lowest in May (0%) as opposite to what was observed in Spain (Ramón et al 1999, Delgado andSilva 2018). Knowing that generally the prevalence of trematodes infecting bivalves as first intermediate host is positively correlated to host size (Magalhães et al 2015), the observed seasonal pattern could be related to the shell length confounding factor. Despite the clams sampled in May (B.…”
Section: Discussionmentioning
confidence: 69%
“…Studies of first host -parasite systems and consequent predictions of disease events are very difficult to accomplish mostly due to generally low prevalence of these parasites and/or sudden high prevalence outbreaks that are followed by mass mortalities (Thieltges et al 2008, Magalhães et al 2015. The effects of the sporocyst, the parasitic stage occurring in the first intermediate host, are often severe and negative impacts are described at the reproduction (Carballal et al 2001), growth (Bowers 1969) and behaviour (Babirat et al 2004) As previously demonstrated by other authors studying other 1 st host-parasite systems (Curtis andHubbard 1990, Magalhães et al 2017), our findings demonstrated that prevalence calculated after host dissection was higher than prevalence calculated by cercariae emergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is among the few reports on large-scale trematode communities infecting cockles (e.g. de Montaudouin et al, 2009;Magalhães et al, 2015) and represents the first large-scale assessment of latitudinal gradient (and abiotic related factors) as a driver of trematode communities composition in Cerastoderma edule as a host model. In addition, this is the first exhaustive study on trematode species composition in Moroccan cockles.…”
Section: Discussionmentioning
confidence: 99%
“…Parasites have been shown to interfere significantly with host populations (reviewed in Magalhães et al, 2015) by initiating diseases that affect reproduction in complex manners, as well as affecting absolute host population numbers (see Fig. 3).…”
Section: Population-level Effectsmentioning
confidence: 99%